2006
DOI: 10.1007/s00024-006-0069-3
|View full text |Cite
|
Sign up to set email alerts
|

Caveats in Multi-modal Inversion of Seismic Surface Wavefields

Abstract: We consider several examples demonstrating that the formal modal representation of surface wavefields often does not describe adequately observable wave parameters, such as the phase and group velocity dispersion of higher modes. The main reason for this is the existence in the medium of several waveguides or weakly coupled wavefields in the same waveguide. In such cases the separation of neighboring higher modes may be impossible, and observed dispersion curves may significantly differ from the ones predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…The purpose is to mimic properties shown by the real data examples that will be introduced in the next section. With reference to Table , the earth model A05 is a four layer model after Asten et al (), the earth model LP06 is a two layer model after Levshin and Panza (), while the earth model L02 is a six layer model after Liang et al ().…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose is to mimic properties shown by the real data examples that will be introduced in the next section. With reference to Table , the earth model A05 is a four layer model after Asten et al (), the earth model LP06 is a two layer model after Levshin and Panza (), while the earth model L02 is a six layer model after Liang et al ().…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
“…In the case of high stiffness contrasts (Park et al ), fundamental mode dominance may be restricted to certain frequency ranges only and at normal sites with velocity increasing with depth the assumption that observed dispersion is dominated by the fundamental mode at all frequencies should be taken with caution. In contrast, in the case of velocity inversions, higher mode dominance is more frequently recognized (Forbriger ) and it is often difficult to accomplish satisfactory resolution for layers below the low velocity layer (Liang et al ), a problem that is well‐known in seismology (i.e., the ‘channel waves’ effect) due to low velocity zones in the upper mantle (Levshin and Panza ).…”
Section: Introductionmentioning
confidence: 99%
“…As is known, modal phase velocities are the only possible solutions of the Rayleigh‐wave eigenvalue problem. Particularly, in the presence of low‐velocity zones or velocity inversions (Kerry 1981; O'Neill et al 2003; Levshin and Panza 2006), higher modes may propagate with more energy than the fundamental mode and become dominant.…”
Section: Description Of the Algorithmmentioning
confidence: 99%
“…Such higher-mode domination was demonstrated using models with high shear-wave velocity contrasts (Levshin and Panza, 2006;Cercato et al, 2010). One of the models suggested by Levshin and Panza (2006) consisted of two layers (Table 1) and had high contrast for both shear (V s ) and compressional (V p ) wave velocities. The 2-layer model parameters were used by two different modeling algorithms.…”
Section: Introductionmentioning
confidence: 92%
“…However, some researchers have reported that at some sites higher-mode energy can dominate over the fundamental mode at the low-frequency end of the spectrum (Park et al, 2005b, Ivanov et al, 2009. Such higher-mode domination was demonstrated using models with high shear-wave velocity contrasts (Levshin and Panza, 2006;Cercato et al, 2010). One of the models suggested by Levshin and Panza (2006) consisted of two layers (Table 1) and had high contrast for both shear (V s ) and compressional (V p ) wave velocities.…”
Section: Introductionmentioning
confidence: 93%